Effects of evaluating dried distillers grains with solubles as a replacement for soybean meal in Boer goat grower rations - Marshall, Micah E.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
There is insufficient data available regarding the role of feeding dried distillers grains (DDGS) with solubles as a replacement for soybean meal (SBM) as a protein source in goat diets. With the growing population of goats in Kansas, DDGS provides an opportunity to utilize a cost-effective resource. The goat population has grown 7.6% in the last year in Kansas and with the readily available access to DDGS, it proves an economic advantage for producers. The objective of this experiment was to evaluate the efficacy of DDGS as a replacement for SBM in a Boer goat diet. Forty-eight meat goat kids, approximately 70 d of age and weighing 28.2 kg were used in a completely randomized design. Animals were housed at the KSU Sheep and Meat Goat Center with 3 kids per pen and 4 pens per treatment. Kids were assigned into one of four experimental diets: 1) 0% SBM replaced by DDGS; 2) 33% SBM replaced by DDGS; 3) 66% SBM replaced by DDGS; and 4) 100% SBM replaced by DDGS. The diet was pelleted and contained roughage, so no supplemental forage was needed. All diet treatments were pelleted at the Kansas State University feed mill. Goats and feeders were weighted weekly over a 47 day period to determine ADG, ADFI, and G:F for each week and for the whole experiment. After 61 days, two goats from each pen were slaughtered at USDA facility and carcass data was collected data was analyzed using GLIMMIX procedure of SAS with pen serving as the experimental unit. The model included effects of the level of DDGS with P-value ≤ 0.05 considered significant. It was found that there was no impact on carcass characteristics. Dietary treatment was found to impact (p<0.001) G:F the greatest. Overall ADG and ADFI was not effected (p<0.05). In conclusion, it was found DDGS can replace SBM with no negative impacts on carcass characteristics or ADG, ADFI, or G:F. It was observed in goats fed diets with 66% or 100% inclusion rate DDGS had a more efficient G:F than those fed a 0% or 33% inclusion rate diet.
Keywords: Spring 2018